Neurodiversity and entrepreneurship - Markel, Karen S.; Hanson, Matthew E.; Giannantonio, Cristina M.; Hurley-Hanson, Amy E. (Emerald studies in workplace neurodiversity, 2024)
Neurodiversity and Entrepreneurship increases our understanding of how different types of entrepreneurial activity may help to improve the inclusion of neurodiverse individuals in the workplace and society. Providing new contributions to the disability literature, research on autism in the workplace, and the intersection of entrepreneurship and neurodiversity, the chapters in this book focus on the various ways entrepreneurship is emerging to improve the careers of neurodiverse individuals, their positive impact on society, and how different types of entrepreneurship manifest themselves across career stages and in the workplace of the future. This is an essential resource for scholars studying neurodiversity in the workplace, organizations interested in obtaining the benefits of hiring neurodiverse individuals, advocacy groups supporting the transition and employment needs of neurodiverse individuals, and neurodiverse individuals, their families, and caregivers. The individual, organizational, and societal issues associated with neurodiversity in the workplace underscore this topic's importance for academics, practitioners, the neurodiverse community and our collective economic well-being and quality of life.